2014
DOI: 10.1002/jbm.b.33117
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and antibacterial properties of Tobramycin loaded hydroxyapatite coated fixation pins

Abstract: The present study investigates the use of nanoporous, biomimetic hydroxyapatite (HA) coatings deposited on TiO₂ coated fixation pins as functional implant surfaces for the local release of Tobramycin in order to prevent bacterial colonization. The impact of HA-coating thickness, coating morphology and biomechanical forces during insertion into synthetic bone on the drug loading and release properties are analyzed. The coatings are shown to exhibit bactericidal effects against Staphylococcus aureus in agar medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…The results obtained in the current study demonstrated biomechanical resistance of the HA coating during insertion in-vivo. This has also been shown with the same type of biomimetic HA coatings in-vitro on external fixation pins by using different synthetic bone qualities [47] [48]. Nevertheless in-vivo proof was lacking in these studies.…”
Section: Discussionmentioning
confidence: 78%
“…The results obtained in the current study demonstrated biomechanical resistance of the HA coating during insertion in-vivo. This has also been shown with the same type of biomimetic HA coatings in-vitro on external fixation pins by using different synthetic bone qualities [47] [48]. Nevertheless in-vivo proof was lacking in these studies.…”
Section: Discussionmentioning
confidence: 78%
“…In more recent years, grit‐blasted and mesoporous materials, such as hydroxyapatite (HA), have been also loaded with gentamicin and tobramycin . The release and efficacy of vancomycin hydrochloride, cephalothin sodium, amoxicillin and carbenicillin sodium salts have been also tested when incorporated in HA coatings .…”
Section: Antimicrobial Coatingsmentioning
confidence: 99%
“…Within the foam structure, the delaminated HA-B fragments showed a flake like morphology, which reflects the "as-deposited" coating morphology [15]. The size of delaminated HA-B fragments, Figure 2(c), is comparable to those observed during conventional scratch testing of the TiO 2 /HA-B coating system [32].…”
Section: Coating Thicknessmentioning
confidence: 54%
“…Biomechanical properties were evaluated using polyurethane (25 PU) foam blocks (20 mm × 20 mm × 4 mm) mimicking spongy bone quality. 25 PU was chosen, since preliminary tests demonstrated that this particular grade induced more severe coating wear-effects after insertion compared to higher density synthetic bone qualities reflecting cancellous bone structures [32]. Three fixation pins of each sample type were loaded with Tobramycin via adsorption at room temperature, denoted as HA-B_RT_BML, or under elevated temperature and pressure, denoted as HA-B_PHT_BML followed by biomechanical insertion.…”
Section: Insertion Into Polyethylene Foammentioning
confidence: 99%